1983
DOI: 10.1002/bit.260250402
|View full text |Cite
|
Sign up to set email alerts
|

The deposition of bacterial cells from laminar flows onto solid surfaces

Abstract: In a previous article, the authors proposed a simple model for the rate of removal of bacterial cells from solid surfaces by fluid shear. This Model has been extended to include the deposition of cells from a flowing suspension. The theory is compared to experimentally obtained data for the deposition of Bacillus cereus cells onto the surface of glass capillaries. The effect of a hydrophobic surface, siliconized glass, and the addition of an antifoam agent to the suspension is also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…At the end of the experiments, the biofilm thickness at the top and the bottom of the membrane tube were 1.83 and 0.82 mm for the JS150 biofilm and 1.21 and 1.07 mm for the GJ10 biofilm, respectively. Similar phenomena were reported previously and have been explained as the result of mixing conditions on the biomedium side of the module, and the concentration of suspended biomass in the biomedium (Buffiere et al, 1995;Freitas dos Santos and Livingston, 1995a;Powell and Slater 1983). The biofilm developed more uniformly in Run 3 in which a lower starting biomass concentration was used.…”
Section: Biofilm Thicknesssupporting
confidence: 87%
“…At the end of the experiments, the biofilm thickness at the top and the bottom of the membrane tube were 1.83 and 0.82 mm for the JS150 biofilm and 1.21 and 1.07 mm for the GJ10 biofilm, respectively. Similar phenomena were reported previously and have been explained as the result of mixing conditions on the biomedium side of the module, and the concentration of suspended biomass in the biomedium (Buffiere et al, 1995;Freitas dos Santos and Livingston, 1995a;Powell and Slater 1983). The biofilm developed more uniformly in Run 3 in which a lower starting biomass concentration was used.…”
Section: Biofilm Thicknesssupporting
confidence: 87%
“…It must be noted that biofilm formation on the carrier particles was not merely retarded by the high shear conditions, eventually stabilizing at a reduced total biomass concentration, as is generally reported (Duddridge et al, 1982;Lau and Liu, 1993;Powell and Slater, 1983). Instead, most of the biomass attached to the particles during the first 10 days thereafter detached again (Fig.…”
Section: P Putida Biofilm Formationmentioning
confidence: 80%
“…This is supported by the observation of Sjollema et al (1988) that desorption of Streptococcus salivarius cells occurred only during the first 5-10 s after deposition. Powell and Slater (1983) reported that the relative number of Bacillus cereus cells with short residence times (<10 s) on the surface of clean glass capillaries was significantly reduced under higher shear stress, together with the total number of adhering cells.…”
Section: P Putida Adhesion Studiesmentioning
confidence: 98%
“…'6 They concluded that this was due to a decreased amount of time spent by the cell in the vicinity of the surface resulting in a reduced ability to bond irreversibly to the surface through exopolymer bridging. 26 Other groups, however, have observed increased colonization of rougher s u b~t r a t u m .~~ It has recently been pointed out that little conclusive evidence is currently available to quantify the effect of substratum surface roughness on biofilm for ma ti or^^',^^ and further examination is required to establish a clear trend.…”
Section: Discussionmentioning
confidence: 99%